Strain tomography of polycrystalline zirconia dental prostheses by synchrotron X-ray diffraction - Korsunsky, A; Baimpas, N; Song, X; Belnoue, J; Hofmann, F; Abbey, B; Xie, M; Andrieux, J; Buslaps, T; Neo, T (2011)
Non-destructive, quantitative and precise determination of internal strain distributions within structural materials and components can be accomplished by only a few experimental techniques, amongst which diffraction of penetrating radiation (X-ray and neutron beams) plays a central role. However, due to the various limitations of these methods, the 2-D and 3-D mapping of internal strains within bulk cross-sections at a spatial resolution of 0.1 mm or better has long remained a challenge. The principle of "strain tomography" proposed by the present authors (an instance of broader "rich" tomography methodology) makes use of the reconstruction tomography technique widely employed in imaging applications. In the present paper we report successful practical implementation of this principle to the study of bending strains in sintered polycrystalline zirconia used in the fabrication of multi-unit fixed prosthetic dentures. The results demonstrate the power of the technique, and pave the way to wider application of this approach to cross-sectional strain mapping in complex-shaped components under various loading conditions. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.